Realtime, Wi - Fi enabled biopotential monitor with adjustable gain and bandwidth using the ESP32 - Arnþór Gíslason 1988- (2018)
This report documents the design, build and characterization of a biopotential amplifier intended to be used as lab equipment for the college level course, Instruments and Vital Signs at Reykjavik University. It consists of two quad op-amps that are used to form an instrumentation amplifier, high pass, low pass and notch filters. Quad digital rheostats allow the user to adjust the bandwidth and an ESP32 samples the signal and transmits it over Wi-Fi with using the WebSockets protocol. A multi-platform jQuery powered script allows visualizing the signal in a browser on a smart device. The device was built as cheaply as possible to minimize the cost for students which required cutting corners. Háskólinn í Reykjavík